Sentiment Analysis on the Application of Tabungan Perumahan Rakyat (TAPERA) Policy in Indonesia - Dzulfikar, Naufal (Department of Informatics Engineering, 2025)
Tapera is a program provided by the Indonesian government with the aim of providing poor people with decent housing, by charging all working classes with salaries above the Regional Minimum Wage of 3% for Tapera contributions. Even though it seems that this program aims to help poor people, this has given rise to a new polemic, which can be seen from some people who don't like this, as can be seen from several negative comments on social media, one of which is X or Twitter. The purpose of writing this paper is to find out whether the sentiment of the TAPERA policy is positive or negative for Indonesians citizens that affected by the policy, with the aim that the author can provide recommendations for government also encourage the usage of Social Media Analytics on government sector in Indonesia, even the result of the sentiment analysis is majority positive or majority negative. This research is conducted by collecting data from Twitter and then processed in such a way, and later will be checked for sentiment analysis with the naive bayes method. From 742 datasets that got from Twitter (after getting sortied, previously, 1680 data was get), it shows that there are 651 tweets that have negative sentiments, and 91 tweets have positive sentiments, which shows how people are disappointed with the TAPERA policy.